FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEIKUTSERTAAN PRIA DALAM PROGRAM KB DI BPM BIDAN A PALMERAH JAKARTA BARAT TAHUN 2017 - Bunga Tiara Carolin; Dwi Junita Priandani (Jurnal Ilmu dan Budaya, 2018)
The Indonesia Demographic and Health Survey 2012 shows that male participation in family planning was still relatively low, both using modern family planning tools and traditional family planning tools. The use of a male contraceptive method was 4.7 percent and decreased from 5.4 percent in the result of Indonesia Demographic and Health Survey 2007. This study aimedto find out the factors related to the participation of males in family planning program. The design of this study using cross sectional approach implemented in Clinic A in April-July 2017 by using questionnaires. Sample in this research were married men who came to BPM A which were 89 participants. This study used univariate and bivariate analysis. The results showed that minority of respondents who participated in family planning program which was equal to 18.0% and who did not participate was 82.0%. From the results obtained, education factor (p=0,002), number of children (p=0,348), knowledge (p=0,000), social culture (p=0,000) and support ofspouse (p=0,000). Conclusion from this research, there was a significant relationship between education, knowledge, socioculture and support of spouse with male participation in family planning, and there was no relationship between number of children and male participation in family planning. From this research, it is expected that health workerscan improve family planning service especially for male by giving motivation counseling for them about family planing program, thus increasing the role of man to join family planning program.